THE CORRELATION OF MONEY SUPPLY AND ECONOMIC GROWTH IN AN ISLAMIC ECONOMICS PERSPECTIVE - Binti Nur Asiyah; Mohammad Fadhilah Hamzah; Sheilla Ayu Amandasari; Shenia Erika Maharani; Dyah Wulandari (Al-Muhasib: Journal of Islamic Accounting and Finance, 2024)
Abstract: This article aims to examine the correlation between the amount of money in circulation and economic growth using the perspective of Islamic economics. The amount of money in circulation is the total value of money in the hands of the community. So, the volume of money circulation in society correlates with the economic growth of a country. This research uses qualitative methods and is included in the category of literature research. The results of the study show that the correlation between money growth and economic growth has a positive influence. The amount of money in circulation and economic growth has a one-way relationship. The relationship between money growth and economic growth is associative. If money growth increases, economic growth will also increase. Likewise, when money growth decreases, economic growth also decreases.   Abstrak: Artikel ini bertujuan untuk meninjau dari korelasi antara jumlah uang yang beredar dengan pertumbuhan ekonomi menggunakan sudut pandang ekonomi Islam. Jumlah uang beredar adalah nilai total uang di tangan masyarakat. Jadi, volume peredaran uang di masyarakat memiliki korelasi dengan pertumbuhan ekonomi suatu negara. Penelitian ini menggunakan metode kualitatif dan masuk dalam kategori penelitian kepustakaan. Hasil penelitian menunjukkan bahwa korelasi antara pertumbuhan uang dan pertumbuhan ekonomi memiliki pengaruh positif. Jumlah uang yang beredar dengan pertumbuhan ekonomi memiliki hubungan yang searah. Hubungan antara pertumbuhan uang dengan pertumbuhan ekonomi bersifat asosiatif. Jika pertumbuhan uang meningkat, pertumbuhan ekonomi juga akan meningkat. Begitu juga ketika pertumbuhan uang menurun, pertumbuhan ekonomi juga menurun.